The Use of Word Maps in Vocabulary Development of the Eleventh Grade Students of SMA Negeri 1 Sindue - Nizam, Moh; Nadrun, Nadrun; Hasyim, Zarkiani (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to examine the effectiveness od using the Word Maps technique on students’ vocabulary development of the eleventh grade at SMA Negeri 1 Sindue. The study employed a quasi-experimental design involving two classes: an experimental class taught using Word Maps and a control class taught using conventional method. The participants were selected through purposive sampling, consisting of 26 students in the experimentsl class and 29 students in the control class. Data were collected using pre-test and post-test, which assessed vocabulary knowledege in terms of meaning, spelling, synonyms/antonyms, and word usage in context. The results revealed that the experimental class class mean score improved significantly from 44.71 to 62.01, while the control class only improved slightly from 44.13 to 47.67. The independent sample t-test indicated ɑ p-value of 0.001 0.05, confirming a statistically significant difference between the two classes.